Design and Therapeutic Potential of 2,5-substituted diphenyl-1,3,4-oxadiazole Derivatives (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
In the present study, new class of 2,5-substituted diphenyl-1,3,4-oxadiazole derivatives were developed by combining substituted aromatic acids with hydrazine hydrate in the presence of POCl3 reagent under various reaction conditions. The compounds were also evaluated for their antimicrobial potential against some bacteria (E. coli and S. aureus) and fungi (C. albicans and A. Niger). As the result of the newly synthesized compounds were characterized as 2-(4-chlorophenyl) compounds-5-(4-nitrophenyl)-1,3,4-oxadiazole (13), 2-(4-methylphenyl)-5-(4-nitrophenyl)-1,3,4-oxadiazole (16), 2-(4-chlorophenyl)-5-(4-methoxyhenyl)-1,3,4-oxadiazole (17), 4-[5-(4-methoxyphenyl)-1,3,4-oxadiazol-2-yl]phenol (18), and 2-(4-chlorophenyl)-5-(2,4-dichlorophenyl)-1,3,4-oxadiazole (25). The results also revealed that these compounds have good potential to inhibit microbes. It may be concluded that oxadiazole nucleus may be a profitable source for the synthesis of drugs against infectious diseases.